Implementasi Media Digital YouTube dalam Pembelajaran PJOK Materi Senam Irama untuk Mengembangkan Keterampilan Motorik Siswa Kelas V di SD Negeri 009 Sangatta Utara - Husnaeni Husnaeni; Anggra Prima; Jumrianah (Civiliza Publishing, Indonesia., 2026)
This study aims to describe the implementation of YouTube digital media in physical education (PJOK) learning, identify the obstacles encountered, and explain the solutions used to develop the motor skills of fifth-grade students at SD Negeri 009 Sangatta Utara. This study used a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation involving the principal, PJOK teachers, and fifth-grade students. Data were analyzed through data condensation, data presentation, and conclusion drawing, while data validity was ensured through triangulation techniques. The results showed that the implementation of YouTube digital media was carried out through three stages: planning, implementation, and evaluation. In the planning stage, teachers prepared learning materials and selected appropriate YouTube videos related to rhythmic gymnastics. In the implementation stage, YouTube videos were used as visual learning media to help students observe and practice movements repeatedly. In the evaluation stage, teachers assessed students' motor skills through direct observation during practical activities. The use of YouTube contributed to the improvement of students' motor skills, especially in movement coordination, accuracy, agility, and imitation ability. In addition, students became more active, enthusiastic, and involved in the learning process. Barriers include limited internet access, inadequate facilities, differences in student motor skills, and a lack of confidence among some students. To address these challenges, teachers download videos, use personal devices when necessary, provide step-by-step guidance, and consistently motivate students. Therefore, YouTube can serve as an innovative and effective learning medium to support motor skill development in elementary school students.